Decolonizing the Literature Review: A Relational Approach. (March 2023) - Tynan, Lauren; Bishop, Michelle
As two (ab)Original women, we consider how a relational approach to the literature review can reflect our broader Indigenous and decolonizing research methodologies. In our research training, we have been exposed to dominant literature review models that advocate for researchers to "identify the gaps" and "occupy a territory, " a process (and vernacular) that feels at odds with Indigenous, relational, and decolonizing principles. We intend to apply the teachings we have learned from Indigenous scholars to the literature review process by proposing a reframing of the literature review, to one that is relational.